The Efficacy of Topical or Systemic Antibiotics as Adjuvants to Non-Surgical Periodontal Treatment in Diabetic Patients: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - de Molon, Rafael Scaf [UNESP]; Rodrigues, Joao Victor Soares [UNESP]; Deroide, Mariella Boaretti [UNESP]; da Silva Barbirato, Davi; Garcia, Valdir Gouveia [UNESP]; Theodoro, Leticia Helena [UNESP] (MDPI, 2024)
Background: Periodontitis and diabetes mellitus (DM) exhibit a bidirectional relationship and are globally significant systemic chronic conditions. The utilization of antibiotics alongside non-surgical periodontal treatment (NSPT) has been a subject of investigation in numerous clinical studies involving human subjects. Thus, the objective of this systematic review is to address the following question: “What is the efficacy of scaling and root planing (SRP) associated with antimicrobials in patients with type 2 DM and periodontitis?”. Methods: A systematic review of the literature was conducted encompassing databases such as MEDLINE/PubMed, Scopus, and Web of Science up to July 2024. Additionally, alerts were configured to capture studies published from the initial search until manuscript submission. Randomized clinical trials assessing clinical periodontal parameters in DM patients undergoing SRP and receiving either topical or systemic antibiotics were compared against a control group (SRP only). Two investigators independently screened articles, extracted data, and evaluated their quality. The selection process, study characteristics, risk of bias, impact of antibiotics on clinical parameters, and certainty of evidence were elucidated in both textual and tabular formats. Meta-analysis was performed separately with forest plots generated for treatment modalities, period of evaluation, and type of antibiotics used. Results: Following the analysis of abstracts and full articles, a total of 30 randomized clinical trials were incorporated into this review, comprising 9 studies on the association of topical antibiotics and 21 studies on systemic antibiotic administration. The principal periodontal parameters assessed included probing pocket depth (PPD), clinical attachment level (CAL), plaque index (PI), and bleeding on probing (BoP). Conclusions: Analysis of the results led to the conclusion that adjunctive periodontal treatment with either topical or systemic antibiotics confers subtle clinical benefits. Nevertheless, owing to the heightened emergence of resistant bacteria and potential side effects, the use of antibiotic therapy in periodontal treatment should be judiciously administered.
Keywords: antibiotics; diabetes mellitus; non-surgical periodontal treatment; periodontal disease